Cattle parasitosis in the Zona da Mata Region of Minas Gerais, Brazil II.Seasonal incidence of lung nematodes - Furlong, John; Novas, José Carlos Vilas; Filho, João Batista Cardoso (Pesquisa Agropecuaria Brasileira, 2014)
In order to study the seasonal incidence of larvae of Dictyocaulus viviparus in pastures, during the period of October 1980 until September 1982, a total of 46 tracer calves were necropsied, at the rate of two per month. The climate of the region allowed development and survival of larvae throughout the year but the greatest incidence occurred during winter, when the average of minimum temperature was 11°C. The most significant factor was low temperature. Larvae ingested in autumm caused the outbreak of infective larvae in pastures in winter.